2023
DOI: 10.3390/toxics11110926
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Profile and Characteristics of Parabens and Alkylphenols in Plasma among Rural Adults in Central China

Qian Gao,
Changsheng Huan,
Yu Song
et al.

Abstract: Parabens and alkylphenols pose serious hazards to human health, yet there are few studies on their exposure profiles and health risks in rural Chinese populations. In this study, 804 participants were selected from the Henan Rural Cohort in mid-eastern China. The plasma levels of parabens (methylparaben, ethylparaben, propylparaben, butylparaben (BuP)) and alkylphenols (4-tert-butylphenol (4-t-BP), 4-tert-octylphenol (4-t-OP)) were analyzed via liquid chromatography–tandem mass spectrometry. Linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…which is confirmed by the fact that PBs concentration levels (especially MeP) noted in the present study are generally higher than values observed in wild animals living especially in less urbanized areas 8 , 18 , 48 . However, PBs are also present in rural areas 49 . The important source of human and animal exposure to PBs in rural regions is connected with the fact that various environmental pollutants, including PBs, are discharged into sewage systems and with the sewage they penetrate into the environment through surface water and groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…which is confirmed by the fact that PBs concentration levels (especially MeP) noted in the present study are generally higher than values observed in wild animals living especially in less urbanized areas 8 , 18 , 48 . However, PBs are also present in rural areas 49 . The important source of human and animal exposure to PBs in rural regions is connected with the fact that various environmental pollutants, including PBs, are discharged into sewage systems and with the sewage they penetrate into the environment through surface water and groundwater.…”
Section: Discussionmentioning
confidence: 99%